The Potential Of Land And Building Tax Revenue In The City Of Bengkulu - Murib, Tindinus; Susena , Karona Cahya (Journal of Applied Financial Management, 2025)
The purpose of this study was to determine the projection of the potential revenue of Land and Building Tax (PBB) in Bengkulu City in 2014-2016. The type of research used in this research is quantitative. The benefit of this research is as an information material to the Local Government of Bengkulu City in policy making and management of Land and Building Tax (PBB) in 2014 to 2016. This research illustrates that the projected revenue potential of Land and Building Tax (PBB) in Bengkulu City has increased from 2014 to 2016. The amount of potential revenue of Land and Building Tax (PBB) in Bengkulu City in 20142016 is consecutively as follows: 2014 amounting to Rp12,285,612,144, 2015 amounting to Rp12,852,211,071, 2016 amounting to Rp.13,418,809,999, This increase in the potential revenue of Land and Building Tax (PBB) will encourage increased realization of PBB revenue for Bengkulu City in the next three years.